Upgrading seismic performance of precast recycled aggregate concrete shear wall using steel-polypropylene hybrid fibers - Gao, Huan; Xu, Lihua; Yu, Min; Yang, Yinjie; Gao, Benhao; Chi, Yin; Huang, Le; Li, Jian; Hong, Jian (Engineering structures, 2025)
In this study, to guarantee the seismic performance of a novel precast shear wall made of recycled aggregate concrete (RAC), the reinforcing technique using steel-polypropylene hybrid fibers (HF) was proposed. To evaluate the applicability of this strategy, nine full-scale precast HF-RAC shear walls were tested subject to in-plane pseudo-static loads. The effects of HF-RAC characteristics, i.e., fiber type, replacement ratio of recycled coarse aggregate (RCA), and volume fraction of steel fiber were systematically considered. The results indicated that the incorporation of hybrid fibers into precast RAC shear walls significantly enhanced their seismic performance, characterized by greater ductility and energy dissipation capacity, despite the comparable load-bearing capacity to the natural concrete shear wall. Additionally, the hybrid fibers also delayed the occurrence of cracks, reduced crack widths, and minimized the area of crushed concrete. Furthermore, the utilization of RCA weakened the peak load by 18.8 %, the displacement ductility by 35.6 %, and the cumulative energy dissipation of the specimens by 40.5 %. Finally, the analysis of skeleton curves revealed that the addition of HF can effectively mitigate the reduction of bearing capacity caused by the presence of vertical seam in the precast RAC walls, while a higher content of RCA tends to exacerbate this reduction. •Quasi-static cyclic tests were conducted on nine full-scale precast RAC shear walls.•Hybrid fibers markedly enhance the seismic performance of precast RAC shear walls.•A higher content of RCA weakens the seismic performance of precast RAC shear walls.•HF can effectively mitigate the reduction of bearing capacity due to the vertical seam.